If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(-2x + -7) + 3x = -53 Reorder the terms: 4(-7 + -2x) + 3x = -53 (-7 * 4 + -2x * 4) + 3x = -53 (-28 + -8x) + 3x = -53 Combine like terms: -8x + 3x = -5x -28 + -5x = -53 Solving -28 + -5x = -53 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '28' to each side of the equation. -28 + 28 + -5x = -53 + 28 Combine like terms: -28 + 28 = 0 0 + -5x = -53 + 28 -5x = -53 + 28 Combine like terms: -53 + 28 = -25 -5x = -25 Divide each side by '-5'. x = 5 Simplifying x = 5
| -6x-11=-3x+7 | | ((S+1)(4-s^2))=0 | | 72=18e | | 0.05(7t-4)=0.35(t-3)+0.85 | | 33n+60= | | -9y-6x=0 | | x+x+3x-10=180 | | 33n+6= | | 24r+48= | | m^2-3=29 | | 28u+14= | | 19d=57 | | 10/x=65/40 | | 13x+4y=20000 | | 81z+45= | | 90+2x-6+x=180 | | 32=2(w)+2(4+3w) | | 14*e=2*7 | | m+6+(4m+2)= | | 25a=35 | | 4=y+20 | | 110x+10= | | 42t+7= | | 7/x=2/1.8 | | 2(4v-9)-3(v-11)=-52 | | 2x+6+(6x-1)= | | 2x-y+3z= | | 1-2x=5-6 | | 5/-12 | | -7y=-x+12 | | 1-((x-2)/3) | | 3x+-12=3x+-12 |